Rekonstruksjon av isutbreiing gjennom Weichsel i vestlege delar av Rondane - Garnes, Lena Svalastog (The University of Bergen, 2006)
The western margins of The Late Weichselian Fennoscandian Ice Sheet are well established from mapping of marginal moraines and submarine fans. The Late Weichselian Glacial Maximum (LGM) occurred on average close to 20 ka BP along the margins of the Fennoscandian-, Barents-Kara Ice Sheet (Mangerud 2004; Svendsen et al. 2004). The vertical extent at the LGM is, however, more difficult to estimate. This thesis is based on fieldwork in the western part of Rondane Mountains, central Norway. Because of its close relationship to the ice-divide zones during glaciations in the south and the main water shed to the north, the Rondane area has since the 18th century been of interest for scientists. Central Scandinavia is commonly thought of as having been continuously ice covered from the end of the last interglacial period, the Eemian and throughout the Weichselian. The earlier widely held assumption, that glacial, as well as wastage features, all belong to the last glaciation and deglaciation, is not supported by this thesis. Erosional lateral drainage channels, accumulated glaciofluvial material and De Geer moraines are common and suggest a vertical downwasting ice mass. The general drainage has been towards north-east. The thesis presents a suggested glacial chronology for the Weichselian in the study area, divided into three glacial phases, with maximum vertical extent during the Early Weichsel, and more limited extent throughout the two other periods, the Mid- and Late Weichselian. The ice-free periods are dominated by periglacial acitivity and permafrost. The ice marginal zone from LGM is found at altitude of c. 1200 m a.s.l in western Rondane. This support earlier investigation from east- and central parts of Rondane (Dahl et al. 1997; Bøe et al. 2006). This view is in conflict with the general assumption that the maximum Weichselian glaciation took place during the Late-Weichselian.